2017
DOI: 10.1136/heartasia-2016-010872
|View full text |Cite
|
Sign up to set email alerts
|

Normal echocardiographic mitral and aortic valve thickness in children

Abstract: We have described a standardised method for mitral and aortic valve measurement in children which is objective and reproducible. Normal ranges of left heart valve thickness in a high prevalence RHD population are established. These results provide a reference range for school-age children in high prevalence RHD regions undergoing echocardiographic screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…This is despite the fact the AMVL thickening had an objective measure (of >3 mm) while AV thickening was a subjective observation. Webb and colleagues found similarly high inter-observer agreement in relation to MV thickness measurements with an inter-class correlation coefficient of 0.85 27. They applied the same strict methodology as described in the WHF diagnostic guidelines 7…”
Section: Discussionmentioning
confidence: 83%
“…This is despite the fact the AMVL thickening had an objective measure (of >3 mm) while AV thickening was a subjective observation. Webb and colleagues found similarly high inter-observer agreement in relation to MV thickness measurements with an inter-class correlation coefficient of 0.85 27. They applied the same strict methodology as described in the WHF diagnostic guidelines 7…”
Section: Discussionmentioning
confidence: 83%
“…Continuous-wave Doppler interrogation of regurgitation was performed to assess peak velocity, duration through the cardiac cycle and spectral envelope. Valve leaflet morphology and thickness was assessed in parasternal long axis (mitral and aortic) and parasternal short axis views (aortic valve) using previously described methods [25] . Images were electronically stored in DICOM format.…”
Section: Methodsmentioning
confidence: 99%
“…While the difference in the behaviour of these features in normal and pathological situations is well described in the WHF Guidelines [3], other articles indicate that some criteria could be improved to reduce inter and intra observer differences. One article in particular found that there were no significant statistical differences in the measurement of the leaflet whether at the tip or the midpoint [7], a result affected by a lack of clearly defined metrics or points of measurement of the leaflet, when analysing the leaflet's thickness.…”
Section: Screening Protocolsmentioning
confidence: 99%
“…This disease starts manifesting at a young age, and it is estimated that over 400.000 annual cases in children (ages [5][6][7][8][9][10][11][12][13][14] in less developed countries, while little over 22.000 annual cases in more developed countries [2]. These numbers show how this disease's burden is mostly shouldered by less developed countries.…”
Section: Introduction 11 Motivationmentioning
confidence: 99%
See 1 more Smart Citation